Variable exhumation history between the central and eastern Xigaze fore‐arc basin, south Tibet: Implications for underthrusting Indian slab dynamics. (7th April 2021) - Ma, Zeliang; Li, Guangwei; Xu, Zhiqin; Kohn, Barry; Zheng, Yilong
Abstract: The Xigaze fore‐arc basin in southern Tibet records important information related to subduction of the Neo‐Tethys and subsequent collision between India and Asia. We present field observations, together with new apatite fission track and zircon (U‐Th)/He (ZHe) thermochronology data, from a 25 km SW‐NE transect in the central Xigaze fore‐arc basin around Sangsang to elucidate the burial and exhumation history. The data indicate that most samples were thermally reset to varying degrees following deposition, with the data and inverse thermal history modelling showing a general northward younging age trend and northward propagation of exhumation. This pattern is comparable with that reported previously from the eastern Xigaze fore‐arc basin. However, variations in exhumation history, stratigraphic exposure and structural characteristics between the eastern and central Xigaze fore‐arc basin are considered to reflect spatially different responses along the southern Asian margin resulting from variations in compressional stresses within the India–Asia collisional zone.